GABAA receptor subtypes and benzodiazepine use, misuse, and abuse - Engin, Elif (Frontiers in Psychiatry, 2023)
Benzodiazepines have been in use for over half a century. While they remain highly prescribed, their unfavorable side-effect profile and abuse liability motivated a search for alternatives. Most of these efforts focused on the development of benzodiazepine-like drugs that are selective for specific GABAA receptor subtypes. While there is ample evidence that subtype-selective GABAA receptor ligands have great potential for providing symptom relief without typical benzodiazepine side-effects, it is less clear whether subtype-selective targeting strategies can also reduce misuse and abuse potential. This review focuses on the three benzodiazepine properties that are relevant to the DSM-5-TR criteria for Sedative, Hypnotic, or Anxiolytic Use Disorder, namely, reinforcing properties of benzodiazepines, maladaptive behaviors related to benzodiazepine use, and benzodiazepine tolerance and dependence. We review existing evidence regarding the involvement of different GABAA receptor subtypes in each of these areas. The reviewed studies suggest that ꭤ1-containing GABAA receptors play an integral role in benzodiazepine-induced plasticity in reward-related brain areas and might be involved in the development of tolerance and dependence to benzodiazepines. However, a systematic comparison of the contributions of all benzodiazepine-sensitive GABAA receptors to these processes, a mechanistic understanding of how the positive modulation of each receptor subtype might contribute to the brain mechanisms underlying each of these processes, and a definitive answer to the question of whether specific chronic modulation of any given subtype would result in some or all of the benzodiazepine effects are currently lacking from the literature. Moreover, how nonselective benzodiazepines might lead to the maladaptive behaviors listed in DSM and how different GABAA receptor subtypes might be involved in the development of these behaviors remains unexplored. Considering the increasing burden of benzodiazepine abuse, the common practice of benzodiazepine misuse that leads to severe dependence, and the current efforts to generate side-effect free benzodiazepine alternatives, there is an urgent need for systematic, mechanistic research that provides a better understanding of the brain mechanisms of benzodiazepine misuse and abuse, including the involvement of specific GABAA receptor subtypes in these processes, to establish an informed foundation for preclinical and clinical efforts.